Exploring Solidarity in Action: Key Methodological Features for Collaborative Research in Physical Education - Rufino, Luiz Gustavo Bonatto; Iannucci, Cassandra; Hunuk, Deniz; Vidoni, Carla; Luguetti, Carla Nascimento; Goncalves, Luiza Lana; Ferreira, Heidi Jancer; Batista, Paula; Borges, Cecilia; Macphail, Ann; Neto, Luiz Sanches; Neto, Samuel de Souza [UNESP] (Human Kinetics Publ Inc, 2024)
Purpose: This paper delves into the approach of solidarity in action as a collaborative research methodology in the field of physical education, based on Freire's concepts of solidarity and circle of culture. In a landscape marked by competitiveness and hierarchy, this paper emphasizes the importance of mutual understanding, empathy, and collective struggle for social change in academia. Results: The paper explores a case study of an international project and highlights three key features: (a) intentionality in group creation, (b) levels of collaboration and horizontal relationships, and (c) democratic facilitation. These features stress the importance of collective action, open dialogue, and shared responsibility. Solidarity in action emerges as a methodology designed to cultivate communities, promote critical engagement, and address social injustices. Conclusion: By integrating solidarity in action into research, the paper advocates for a more inclusive, equitable, and culturally sensitive approach in physical education, highlighting the potential for positive change in academia.
Keywords: collaboration; internationalization; innovative collaborative methodologies; Paulo Freire